Preparing for Genocide: Quasi-Experimental Evidence from Rwanda - Evelina Bonnier; Jonas Poulsen; Thorsten Rogall; Miri Stryjan (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2016)
This paper provides evidence for how an authoritarian state can mobilize civilians to participate in mass violence through a top-down policy. We analyze a Rwandan mandatory community program that required citizens to participate in community work and political meetings every Saturday in the years before the 1994 genocide. We exploit cross-sectional variation in meeting intensity induced by exogenous weather fluctuations, and find that a one standard-deviation increase in the number of rainy Saturdays resulted in a 16 percent lower civilian participation rate in genocide violence. The natural placebo test – rainfall on all other weekdays – yields no statistically significant results. Moreover, the result is entirely driven by areas under the control of pro-Hutu parties, and we find evidence that the political elites used the program beyond simple propaganda, bringing civilians together and practicing mobilization. We also present suggestive evidence that in areas with opposition parties in power, the effects turn positive, implying that the meetings there were used to overcome hatred. Our robust findings shed light on the potentially detrimental role of government-ordered community meetings. Its importance derives, at the very least, from the resurgence of similar practices in sub-Saharan Africa.
Keywords: D74; N47; 330; Conflict; Rainfall